KRITIK SASTRA FEMINIS DALAM NOVEL THE PERFECT WORLD OF MIWAKO SUMIDA SEBAGAI ALTERNATIF BAHAN AJAR MENGANALISIS ISI SERTA KEBAHASAAN NOVEL PADA KELAS XII SMA - Khairunnisa Fitriany Yustikasari; Dindin M.Z.M; Lili Sadeli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the content, structure, and linguistic elements in the novel The Perfect World of Miwako Sumida by Clarissa Goenawan; knowing the feminist literary criticism found in the novel The Perfect World of Miwako Sumida by Clarissa Goenawan as an alternative teaching material in learning Indonesian at the high school level. The method used in this research is descriptive qualitative. Data collection techniques used include writing and reading techniques. The research results are: first, the content, structure, and linguistic elements contained in the novel The Perfect World of Miwako Sumida by Clarissa Goenawan have been fulfilled. This can be proven because there are stories, abstract structures, orientations, complications, evaluations, resolutions, and coda. In the novel there are also intrinsic elements in the form of characters, characterizations, plot, setting (place, time, atmosphere), point of view, and message. In the novel there are also linguistic rules in the form of the use of direct sentences, past sentences, material verbs, mental verbs, temporal conjunctions, and adjectives. Second, feminist literary criticisms contained in the novel The Perfect World of Miwako Sumida by Clarissa Goenawan have been fulfilled. This can be proven, because there is gender marginalization, gender subordination, gender stereotypes, gender violence, and gender workload. Third, the feasibility of the results of the analysis to be utilized as teaching materials. Based on these results the researcher concluded that, some of the findings in this analysis can be used and utilized for learning materials because they are in accordance with the demands of an independent curriculum or in accordance with Learning Outcomes.